1-Ethyl 2-methyl 3,4-bis(acetyloxy)pyrrolidine-1,2-dicarboxylate: crystal structure, Hirshfeld surface analysis and computational chemistry - Dallasta Pedroso, Sofia; Caracelli, Ignez; Zukerman-Schpector, Julio; Soto-Monsalve, Monica; De Almeida Santos, Regina H.; Correia, Carlos Roque D.; Llanes Garcia, A. L.; Kwong, Huey Chong *; Tiekink, Edward R. T. * (International Union of Crystallography, 2020)
The title compound, C13H19NO8, is based on a tetra-substituted pyrrolidine ring, which has a twisted conformation about the central C—C bond; the Cm—Ca—Ca—Cme torsion angle is 38.26 (15)° [m = methylcarboxylate, a = acetyloxy and me = methylene]. While the N-bound ethylcarboxylate group occupies an equatorial position, the remaining substituents occupy axial positions. In the crystal, supramolecular double-layers are formed by weak methyl- and methylene-C—H...O(carbonyl) interactions involving all four carbonyl-O atoms. The two-dimensional arrays stack along the c axis without directional interactions between them. The Hirshfeld surface is dominated by H...H (55.7%) and H...C/C...H (37.0%) contacts; H...H contacts are noted in the inter-double-layer region. The interaction energy calculations point to the importance of the dispersion energy term in the stabilization of the crystal.